MODELING THE WORK OF THE MUSCLES OF THE LOWER EXTREMITY IN CONDITIONS OF FLEXION-ADDUCTION CONTRACTURE OF THE HIP JOINT AND FLEXION-EXTENSION CONTRACTURE OF THE KNEE JOINT - Bezsmertnyi, Yurii; Branitskyi, Oleksandr; Tyazhelov, Olexiy; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Large joint damage often leads to inability to work and disability that requires long-term treatment. The development of osteoarthritis is accompanied by changes in the muscles and special rehabilitation measures are needed to restore their strength, symmetry of the load during standing and steps during walking. Objective. To determine the most vulnerable muscles of the lower extremities in the conditions of osteoarthritis of the hip and knee joints using a mathematical model. Methods. Three mathematical models were created in the OpenSim system. Model 1 (normal): extension/flexion — 10°/0°/45°; removal/adduction — 5°/0°/12°; rotation — 3°/0°/3°, foot turning — 5°. Model 2 with flexion-adduction contracture of the hip: flexion setup — 20°,adduction setting — 10°, foot turning — 10°, shortening of the femur by 2 cm. Model 3: flexion contracture of the knee joint — 0/20°/50°. Results. With combined hip contracture, the isometric strength of the muscles decreases by almost 60 %. In the case of flexion contracture of the knee joint, the rectus femoris muscle is more stretched and requires 3.5 % more force to extend the knee. In the presence of adductor contracture of the hip joint, the thigh’s thin muscle is in a contractile state, which reduces its strength by almost 90 %. In the case of knee contracture, this muscle is primarily in a stretched state, so more force is required to extend the knee — in our model, by 6 %. With changes in the lower extremity due to the development of hip contracture, the gastrocnemius muscle can lose up to 78 % of its strength, and the knee muscle — up to 5%. In conditions of knee joint contracture, the most vulnerable muscles are the pelvic stabilizer muscles (m. tensor fasciae latae) — a decrease in strength of up to 44.4 %, and the knee (m. semimembranosus) — up to 54.5 %. Conclusions. Contractures of the hip and knee joints lead to a loss of muscle strength of the lower limb, which negatively affects its functioning and recovery after arthroplasty.